IMPLEMENTATION OF PROBLEM BASED LEARNING IN EFFORTS TO INCREASE CLASS V SCIENTIFIC ATTITUDE IN NATURAL SCIENCE LEARNING IN PRIMARY SCHOOL - Wikut Deniarti; Anang Masduki (Universitas Ahmad Dahlan, 2015)
ABSTRACTThis research purpose to increase the scientific attitude in the fifth grade students learning sains through the application of Problem Based Learning in Elementary School Caturtunggal 7 Depok Sleman, Yogyakarta. The subject of this research is the fifth grade elementary school students Caturtunggal 7 Depok, Sleman, amounting to 16 students. This type of research is Classroom action research are held in two cycles of action. Data collection instruments used were sheets of observation, interviews, and camera digital. The validity of the instruments is done through expert judgment. The data have been collected were analyzed by descriptive quantitative and qualitative. Quantitative descriptive analysis was used to compare the percentage of the value of each student step by step. The results showed that with applied Problem Based Learning in sains learning can increase students scientific attitude fifth grade in Elementary school Caturtunggal 7 Depok Sleman, Yogyakarta. This is indicated by the increasing number of students who scored higher than 75% of the initial condition until the second cycle. At the beginning there were 4 students (25%) reached KKM. The average grade achieved is 51.93. In cycle I have 9 students (56.25%) reached KKM. The average grade achieved was 66. In the second cycle there were 13 students (81.25%) reached KKM. The average grade achieved is 77.56.